2015
DOI: 10.20937/atm.2015.28.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Recent warming in the Balearic Sea and Spanish Mediterranean coast. Towards an earlier and longer summer

Abstract: Este trabajo analiza los cambios recientes en la temperatura del mar Balear y las tierras costeras circundantes. Para el análisis de la temperatura terrestre se han utilizado registros mensuales de varios observatorios litorales del mar (SST, por sus siglas en inglés) se utilizaron imágenes térmicas mensuales de satélite procedentes del Physical Oceanography Distributed Active Archive Center (PO.DAAC) disponibles para el periodo 1985-2009. últimos 25 años, con tasas de 0.039 ºC/año en tierra para el periodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
4
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
5
4
1
1
Order By: Relevance
“…In particular, the results of this study agree with the ones obtained in the Balearic Sea and Spanish Mediterranean coast. In fact, Lopez Garcia () evidenced that between the periods 1960–1980 and 1981–1992 the increase of temperature occurred mainly during the summer and autumn (from July to December), but between the more recent periods, from 1981–1992 to 1993–2010, the increase is especially strong in spring (May and June). Moreover, both on land and at sea during the last decade there seems to be a decrease of temperature in September.…”
Section: Resultssupporting
confidence: 89%
“…In particular, the results of this study agree with the ones obtained in the Balearic Sea and Spanish Mediterranean coast. In fact, Lopez Garcia () evidenced that between the periods 1960–1980 and 1981–1992 the increase of temperature occurred mainly during the summer and autumn (from July to December), but between the more recent periods, from 1981–1992 to 1993–2010, the increase is especially strong in spring (May and June). Moreover, both on land and at sea during the last decade there seems to be a decrease of temperature in September.…”
Section: Resultssupporting
confidence: 89%
“…According to Sánchez-Benítez et al [13], in June 2017, we witnessed the earliest mega-heatwave in the entire reanalysis period, which primarily affected Iberia. The occurrence of such intense and spatially extensive heat events in June in recent years could be an indication of an increasingly warmer, earlier, and consequently, increasingly longer summer across Europe [46][47][48]. June 2019 could be a subsequent manifestation of these changes, which are in agreement with existing climate projections [49].…”
Section: Discussionsupporting
confidence: 82%
“…The temperature of the Atlantic Waters in the EMED showed a significant decreasing trend which would be in contradiction with recent works which analyze satellite SST time series (López-García, 2015;Skliris et al, 2012;Nikjaer, 2009). The lack of 360 significant trends for the temperature of the WMED would also be in contradiction with the study by Salat and Pascual (2006).…”
contrasting
confidence: 97%
“…Finally, Krahmann and Schott (1998) reported positive salinity trends for the AW while Sparnocchia et al 55 (1994) found no changes for the salinity of this water mass. More recent works have evidenced by means of satellite infrared data the warming of the surface layer, both in the Western and Eastern Mediterranean (WMED and EMED) from the mid 1980s to the first decade of the twenty first century (López-García, 2015;Skliris et al, 2012;Nikjaer, 2009).…”
mentioning
confidence: 99%